Modulable and Highly Diastereoselective Carbometalations of Cyclopropenes. Issue 4 (8th January 2014) - Didier, Dorian; Delaye, Pierre‐Olivier; Simaan, Marwan; Island, Biana; Eppe, Guillaume; Eijsberg, Hendrik; Kleiner, Amir; Knochel, Paul; Marek, Ilan
Abstract Invited for the cover of this issue is the group of Ilan Marek at Technion–Israel Institute of Technology. The image depicts how cyclopropenes can be used to access to a variety of small, quaternary carbon‐bearing chiral building blocks. Read the full text of the article at 10.1002/chem.201303569.